Experiences of Boys and Girls during their Transition to Kindergarten - Rios Catano, Cecilia
This research is concerned with understanding the experiences of a group of children from a private school in the municipality of Caucasia (Antioquia) in their passage through the Transition grade. A qualitative design with a hermeneutic approach was chosen; the narratives of a group of children were the sources for the generation of information and their analysis allowed us to know that for each one of them this passage represents a particular, different meaning: therefore, the experience cannot be planned, anticipated or generalized. It was found that educational transitions are linked to intense emotions, moments of uncertainty, fears, encounters and misunderstandings involving different educational agents, due to changes in the scenario, relationships with new adults, peers, spaces, materials and interactions. It was also found that (1) boys and girls experience grief due to separation from the family and losses related to the kindergarten, (2) the school spaces are places of fun, escape from the teacher's gaze, making certain decisions, encounters, but also fears, resistances and fantasies, (3) the tasks represent expectations, challenges, displeasure and discomfort, (4) the meanings attributed are closely linked to the discourses of the families. Although these expressions related to different feelings appear in what the participants narrate, it is not a question of avoiding suffering or schooling, but rather of accompanying them so that they can make this passage in the best possible way.